(untitled) (Journal of the College of Languages (JCL), 2022)
The present paper discusses one of the most important Russian linguistic features of Arabic origin Russian lexes denoting some religious worship or some political and social positions like Qadi, Wally, Sultan, Alam, Ruler, Caliph, Amir, Fakih, Mufti, Sharif, Ayatollah, Sheikh.. etc. A lexical analysis of the two of the most efficient and most used words of Arabic origin Russian lexes that are “Caliph and Sheikh” is considered in the present study. The lexicographic analysis of these words makes it possible to identify controversial issues related to their etymology and semantic development. The study is conducted by the use of the modern Russian and Arabic dictionary, specifically, (Intermediate lexicon Dictionary) where many linguistic terms borrowed from Arabic into Russian have been identified. A comparative study of lexical Data used in Russian dictionaries and that of Arabic dictionary (Intermediate lexicon Dictionary) shows significant differences in their lexical modeling. The present study provides a lexical analysis and shows the semantic, grammatical and spelling acoustic of Arabic adapted words in Russian discourse. It is safe to say that through another intermediate language, large number of Arabic lexes have, directly and indirectly, been used in Russian, something clearly modeled in Derivative Russian dictionaries. Аннотация В данной работе обьём статьи ограничён, поэтому мы рассматрваем только два найболее эффективных, найболее интересных и найболее уботребительных слов в русском языке, это лексемы хали́ф / кали́ф и шейх, которые известно носителям русского языка и активно функционируют в русской речи. Лексикографический анализ этих слов позволил выявить спорные вопросы, связанные с их этимологией, показать специфику толькований арабизмов и развитие их семантики. На материале документов Национального корпуса русского языка исследовано функционирование иноязычий в речи, определено отношение слов к нарицательной и собственноименной лексике, к терминонологической системе языка-реципиента.